The course of TBT pollution in the world during the last decade - Souto, Márcia Alexandra Miranda (2015)
Organotins (OTs) are organometallic compounds. Despite of the multiple applications of the OTs, the notoriety of these compounds is due to tributyltin (TBT), a potent biocide used in antifouling paints since the 60s to prevent biofouling on submerged surfaces, including the hulls of ships. Despite of the extreme effectiveness of these paints in combating biofouling, they are also extremely toxic to non-target organisms, therefore several legislative measures restricting their use were implemented in several countries worldwide. TBT causes a huge variety of adverse effects on non-target species (sublethal / lethal) of different taxonomic groups (from bacteria to mammals). The first evidence of adverse effects induced by TBT on non-target species emerged in the 70s in oysters of the species Crassostrea gigas in the Bay of Arcachon, France. Their shells have suffered thickening with consequent decrease in the volume of edible portion, reducing its commercial value. In the same decade was verified the occurrence of male sexual characteristics in female prosobranch gastropods (formation of a penis and / or development of a vas deferens), by exposure to TBT. This phenomenon was coined as "imposex" by Smith in 1971. The imposex is the best known example of endocrine disruption caused by a pollutant being used as a biomarker to monitoring the environmental pollution by TBT. The gastropods are used globally for monitoring environmental pollution by TBT. In the present work we studied how gastropods have been used to track the course of TBT pollution worldwide during the last decade (2003-2013), and the main results obtained. We searched for the number of published articles by year / continent and country regarding the bioindicator species most used in biomonitoring TBT pollution in function of their geographical location; we evaluated the efficacy of the AFS Convention in reducing TBT pollution worldwide; we evaluated the temporal evolution (2003-2013) of the levels of imposex by bioindicator species and geographical area, as well as the concentration of OTs in the biota, water and sediments. There was noticed an increase of the number of publications for monitoring environmental pollution by TBT in 2008, coincident with the time of entry into force of the AFS Convention and a gradual decrease of the number of publications from 2008 to 2013, after the entry into force of this Convention; most of the monitoring studies developed in the period 2003-2013 were conducted in Europe, followed by the continents: America, Asia, Africa e Oceania; in this period were used 96 bioindicator species of imposex, being that the 5 more used were: Nucella lapillus, Hexaplex trunculus, Nassarius reticulatus, Stramonita haemastoma and Thais clavigera. A greater diversity of bioindicators was used in America and Asia compared to Europe, whist Africa and Oceania were the continents with smaller number of bioindicator species used. Regardless of the geographic region, and despite the wide diversity of species used, the bioindicators were all caenogastropods (Subclass Caenogastropoda) and most frequently of Order Neogastropoda and Littorinimorpha, being the majority from family Muricidae. There was a decrease of the levels of imposex in the different bioindicators used by continent and country, as well as a decline of the concentrations of OTs in biota, water and sediments, by continent and country, since the entry into force of the AFS Convention in September 2008.